A Contrastive Analysis of Emotive Interjection (Kandoushi) in Japanese and Indonesian - Prasetya Maulana Yasin; Linna Meilia Rasiban; Aep Saeful Bachri (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2022)
Kandoushi is a word that expresses an impression, also called “interjection” in Indonesian, and is one type of emotive interjection. This study examines the meaning and use of emotive interjection, and its similarities and differences in Japanese and Indonesian. The method in this study used a descriptive contrastive analysis method with the note-taking technique. The data is taken from the dialogue in the Japanese anime “ReLIFE” and the Indonesian TV series “Tetangga Masa Gitu” and “Bajaj Bajuri”. The results of the study showed that the emotive interjection in Japanese and Indonesian had several similar meanings, particularly expressing feelings of pleasure, admiration, annoyance, confusion, and distress. Then, both of them have the same use, which is used to confirm the speech partner’s expression, is used to conclude something, is used to protest against the speech partner, is used to show approval, and is used to realize something. Interjection comprehension is very important in understanding an utterance intent in a conversation so that communication can take place with native speakers or fellow foreign students. This study only examines the interjections in terms of the emotive feeling/impression of being surprised. Therefore, for future research, it is expected to research form, meaning, and the use of other interjections in terms of phonology.